Jesus and the Holy City New Testament perspectives on Jerusalem - Walker, Peter W.L. (Grand Rapids, MI Eerdmans, 1996)
Includes bibliographical references and indexes
Keywords: Jerusalem in the Bible; Bible N.T. -- criticism, interpretation etc; Jesus Christ -- views on Jerusalem; Jerusalem in Christianity -- history of doctrines -- early church, ca. 30-600; Bible. N.T. -- criticism, interpretation, etc